Synthesis of SnO2/B-P codoped g-C3N4 nanocomposites as efficient cocatalyst-free visible-light photocatalysts for CO2 conversion and pollutant degradation - Raziq, Fazal; Qu, Yang; Humayun, Muhammad; Zada, Amir; Yu, Haitao; Jing, Liqiang (Applied catalysis. B, Environmental, 2017)
Enhanced visible-light photocatalytic activity of g-C3N4 results from increased optical absorption and charge separation by P-B co-doping and SnO2 coupling. [Display omitted] •SnO2-coupled boron-phosphorus co-doped g-C3N4 nanocomposites have been synthesized.•Nanocomposite exhibits enhanced visible-light activities for pollutant degradation.•Produced hydroxyl radical amounts are agreeable with enhanced photocatalytic activities.•Enhanced activity depends on extended visible-light absorption after co-doping B and P.•Enhanced activity is also attributed to promoted charge separation after coupling SnO2. Coping with the gradually increasing worldwide environmental issues, it is highly desired to develop efficient, cheap and visible-light responsive nano-photocatalysts for CO2 conversion and pollutant degradation. Herein, we have successfully synthesized SnO2-coupled boron and phosphorus co-doped g-C3N4 (SO/B-P-CN) nanocomposites as efficient cocatalyst-free visible-light photocatalysts of low cost for both CO2 conversion and pollutant degradation. It is shown that the amount-optimized SO/B-P-CN nanocomposite exhibits enhanced visible-light activities for CO2 conversion to CH4 from CO2-containing water by ∼9 times, and for phenol and acetaldehyde degradation by ∼7 times, as compared to the bare CN nanosheets. Moreover, it is confirmed that a large amount of produced hydroxyl radicals on SO/B-P-CN is well responsible for the greatly-enhanced photocatalytic activities. Interestingly, the evaluated quantum efficiency (2.02%) of optimized SO/B-P-CN nanocomposite for photocatalytic CO2 conversion at λ=420nm is much higher than other reported result. Mainly based on the surface photovoltage responses and the photocurrent action spectra, it is suggested that the enhanced activity of SO/B-P-CN nanocomposite depends on the extended visible-light absorption from 460 to 550nm after B-P co-doping, and the promoted charge separation via the dopant-induced surface states and the coupled SO nanoparticles. This work implies that the modified CN nanosheets as cheap nanocomposites display promising applications in the photocatalytic field of CO2 conversion to useful fuels and pollutant degradation for environmental remediation.